Prevalence of Barrett’s esophagus and factors associated with the diagnosis of dysplasia or adenocarcinoma in patients evaluated at a Chilean university endoscopy center - Espino, Alberto (2025)
Introduction: Esophageal adenocarcinoma (EAC) is increasing in Western countries, and Barrett’s esophagus (BE) represents its only known premalignant condition. BE affects approximately 1–2% of the general population and up to 14% of patients with gastroesophageal reflux disease (GERD). Data from Latin America and Chile remain limited. Objectives: To determine the prevalence of BE, the neoplasia detection rate (NDR), and the endoscopic quality criteria associated with neoplasia detection in a Chilean university center. Materials and methods: A longitudinal cohort study including all patients with BE identified among upper gastrointestinal endoscopies performed at the Red de Salud UC CHRISTUS between January 2015 and December 2022. Patients with a history of other digestive neoplasms or referred with previously diagnosed BE/EAC were excluded. Demographic, endoscopic, and histopathological variables were analyzed. BE prevalence was defined as the number of histologically confirmed BE cases over the total diagnostic endoscopies performed during the study period. NDR was defined as the presence of highgrade dysplasia (HGD) or EAC on index endoscopy among BE patients. Multivariable logistic regression was applied to identify factors independently associated with NDR. Results: A total of 422 patients were diagnosed with BE (62% men; mean age 58 years, range 17-87). The overall prevalence of BE was 0.46% (422/91,723), increasing from 0.33% in 2015 to 0.72% in 2022. The low-grade dysplasia detection rate was 3.8% (16/422) and the NDR 1.7% (7/422). The mean BE length was 3,7 cm (range 1–18 cm). The Prague classification and chromoendoscopy were reported in 66% (280/422) and 44% (185/422) of procedures, respectively. Factors independently associated with neoplasia detection were age (OR 1.08; 95% CI 1.01-1.16), use of chromoendoscopy (OR 10.1; 95% CI 1.03-96), and presence of a visible lesion (OR 43.7; 95% CI 4.9-393). Conclusion: The prevalence of BE in this Chilean cohort was 0.46%, showing an upward trend approaching international reports. The use of chromoendoscopy and the detection of visible lesions were independently associated with higher neoplasia detection, underscoring the importance of adherence to endoscopic quality standards in BE evaluation.